Predictors of disease-related concerns and other aspects of health-related quality of life in outpatients with inflammatory bowel disease - Mussell, Monika; Böcker, Ulrich; Nagel, Nils; Singer, Manfred V. (European journal of gastroenterology & hepatology, 2004)
Objective - Disease-related concerns are a major dimension of health-related quality of life in inflammatory bowel disease (IBD). The aim of this study was to assess the concerns of IBD patients in an outpatient sample, and to determine the impact of psychological and disease factors on concerns and on other variables of health-related quality of life. - Methods - Seventy-two outpatients with IBD were assessed with regard to disease-related concerns [with the Rating Form of IBD Patients’ Concerns (RFIPC)], psychological symptoms and somatic complaints non-specific to IBD as dependent variables. Coping with illness, health locus of control, and disease variables were assessed as predictor variables. Multiple regression analyses determined the independent contribution of each predictor on the dependent variables. - Results - Women reported more intense concerns than men. No difference in concerns was found between patients with Crohn's disease and ulcerative colitis. The highest predictive value for the RFIPC total score was found for depressive coping. It explained a greater proportion of variance on the RFIPC total score (23%) than demographic (10%) and disease variables (7%), and comparably impinged on RFIPC subscores. Furthermore, depressive coping was significantly associated with psychological distress, the self-rated health status and somatic complaints non-specific to IBD. - Conclusions - Our findings suggest that in IBD psychological variables, particularly depressive coping, are more predictive than medical variables for disease-related concerns and other variables of health-related quality of life. Further studies are needed to examine the effects that the way of coping with disease have on long-term outcome in IBD.